Correlation of Body Mass Index and Disease Activity Score (DAS-28) in Patients with Rheumatoid Arthritis - Nishtha Agarwal; Shweta Dubey; Sanjeev Kapoor; Shriram Garg; AN Malaviya; Puja Nagpal (Medsci Publications, 2024)
Background: Rheumatoid Arthritis (RA) is the most common autoimmune disease. RA can cause permanent deformity and loss of productivity. The primary objective of the study was to evaluate the relationship of BMI with Disease Activity Score in RA patients. The secondary objective was to evaluate the presence of comorbidities such as diabetes, thyroid, hypertension, periodontitis, and pregnancy outcomes (in the case of females) in the RA patients population presented at the tertiary healthcare centre. Method: The presented study was a cross-sectional study. 100 Patients presented to the joint clinic were recruited. RA diagnosis of patients was based on the ACR/ELULAR criteria. Their demographic and clinical data was collected through one-on-one interviews. Results: The recruited population shows that BMI has a moderate positive correlation (r=0.347, p=0.001) with disease activity scores. 51% of RA patients have one or more comorbidities. 45.2 % of female RA patients suffered one or two miscarriages during their pregnancy. It is significantly higher as compared normal female population. Conclusions: Active control of BMI may be required to prevent RA symptom aggravation. RA patients are prone to develop comorbidities and females with RA may need close monitoring during their pregnancy period.